Correlation of protein, vitamin c and iron intake with pre-hemodialysis hemoglobin level in chronic renal failure patients - Andreyas Andreyas; Deri Andika Putra (UHAMKA PRESS, 2021)
Chronic Kidney Disease (CKD) is a kidney damage that causes the kidneys to be unable to remove toxins and waste products from the blood, characterized by protein in the urine and a decrease in the glomerular filtration rate, lasting more than 3 months. The study found the relationship between protein, vitamin C, and iron intake with pre-hemodialysis hemoglobin levels in patients with chronic renal failure in RSUD Harapan dan Doa in the city of Bengkulu. The research design used in this study was observational analytic with cross-sectional approach. Research conducted by approaching, observing, or collecting data at the same time was taken at the same time. The results showed that there was a significant relationship between vitamin C intake (p=0.001), there was a significant relationship between iron intake (p=0.002), there was no significant relationship between protein intake (p=0.013) in RSUD Harapan dan Doa Bengkulu in 2020. Subjects with adequate intake had an impact on positive impact on hemoglobin levels. This is in line with the fact that protein, vitamin C, and iron intake help to increase hemoglobin levels and help to reduce intake while undergoing hemodialysis therapy. It can be concluded that adequate protein, vitamin C, and iron intake are important factors for increasing hemoglobin levels in chronic renal failure patients undergoing hemodialysis.